2022
DOI: 10.1007/s00204-022-03394-z
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of pyrrolizidine alkaloids in metabolically inactive human cervical cancer HeLa cells co-cultured with human hepatoma HepG2 cells

Abstract: Pyrrolizidine alkaloids (PAs) are secondary plant metabolites, which can be found as contaminant in various foods and herbal products. Several PAs can cause hepatotoxicity and liver cancer via damaging hepatic sinusoidal endothelial cells (HSECs) after hepatic metabolization. HSECs themselves do not express the required metabolic enzymes for activation of PAs. Here we applied a co-culture model to mimic the in vivo hepatic environment and to study PA-induced effects on not metabolically active neighbour cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…In the liver, PAs not only damage hepatocytes, but also proximate liver sinusoidal endothelial cells (LSEC), which was attributable to the efflux of reactive metabolites from the hepatocytes and uptake into LSEC (Hessel-Pras et al 2020 ). This has recently also been demonstrated using a co-culture model of HepG2 liver cells and metabolically deficient HeLa cells (Hadi et al 2023 ). It is further noteworthy that PAs can also be transported to other organs such as the lungs, where they can cause toxicity (He et al 2021a ; Song et al 2020 ).…”
Section: Introductionmentioning
confidence: 67%
“…In the liver, PAs not only damage hepatocytes, but also proximate liver sinusoidal endothelial cells (LSEC), which was attributable to the efflux of reactive metabolites from the hepatocytes and uptake into LSEC (Hessel-Pras et al 2020 ). This has recently also been demonstrated using a co-culture model of HepG2 liver cells and metabolically deficient HeLa cells (Hadi et al 2023 ). It is further noteworthy that PAs can also be transported to other organs such as the lungs, where they can cause toxicity (He et al 2021a ; Song et al 2020 ).…”
Section: Introductionmentioning
confidence: 67%
“…Based on our previous work on anti-insulin resistance activity, we first revealed the protein profiling of C3G in the whole proteome of HepG2 cells and found its covalent binding to some target proteins. Due to the good metabolic regulatory activity of anthocyanins, we further verified the protein covalent binding ability in HeLa cells with an equally active metabolism . These results will promote the chemical development of anthocyanin structures.…”
Section: Introductionmentioning
confidence: 61%
“…Due to the good metabolic regulatory activity of anthocyanins, we further verified the protein covalent binding ability in HeLa cells with an equally active metabolism. 28 These results will promote the chemical development of anthocyanin structures. In this work, the clickable alkynyl group was introduced into the A ring of C3G to avoid affecting the activity, 29,30 and the modification of the two phenolic hydroxyl groups was referred to Wang et al 31 As shown in Figure 1A, the covalent binding probe C3G-Probe and the noncovalent photoaffinity probe C3G-Diazirine were obtained based on the synthetic route we developed previously.…”
Section: ■ Introductionmentioning
confidence: 95%
“…The PA-induced disturbances in mitosis may contribute to the formation of micronuclei. Europine, riddelliine, and lasiocarpine induced micronuclei in HepG2 cells [89].…”
Section: Hepatotoxicitymentioning
confidence: 90%